2021
DOI: 10.3390/s21062093
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IoT Actors

Abstract: The Internet of Things (IoT) is a leading trend with numerous opportunities accompanied by advantages as well as disadvantages. Parallel with IoT development, significant privacy and personal data protection challenges are also growing. In this regard, the General Data Protection Regulation (GDPR) is often considered the world’s strongest set of data protection rules and has proven to be a catalyst for many countries around the world. The concepts and interaction of the data controller, the joint controllers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…The elements involved in this model are briefly discussed below. The authors in [18] identified all the components and regulations that are involved in an IoT architecture.…”
Section: Iot Architecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The elements involved in this model are briefly discussed below. The authors in [18] identified all the components and regulations that are involved in an IoT architecture.…”
Section: Iot Architecturesmentioning
confidence: 99%
“…The communication protocols that enable the connectivity to the devices with the core network define the format of the data to be transmitted, the routing used, the flow control and the retransmissions of the lost packets [18]. Table 1 shows the main characteristics of the technologies used in IoT.…”
Section: Iot Communication Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating huge volumes of data makes data management one of the most critical challenges for IoT infrastructures. As fragmentation across the many IoT actors grows, so does the importance of data laws, regulations, and policies [1]. The legal framework of General Data Protection Regulation (GDPR) entered into force in 2016 after passing the European Parliament, and, as of May 25 2018, all organizations are required to be compliant.…”
Section: Introductionmentioning
confidence: 99%
“…In the article “Identification of IoT Actors” [ 7 ], Suada Hadzovic et al focus on clarifying the identification of IoT actors used in one thousand IoT-related standards. Based on the five layers of computing paradigm such as cloud, fog, edge, mist, and dew computing, they define the IoT model by mapping diverse IoT actors as well as IoT components such as a thing, gateway, service, user, etc., which is expected to provide a clearer clarification of the blurred definition of IoT actors and their relationship.…”
mentioning
confidence: 99%